Predictors of Good Clinical Outcome After Endovascular Treatment for Acute Ischemic Stroke due to Tandem Lesion in Anterior Circulation: Results from the ASCENT Study - Havlíček, Roman; Šaňák, Daniel; Černík, David; Neradová, Jarmila; Leško, Norbert; Gdovinová, Zuzana; Köcher, Martin; Cihlář, Filip; Malik, Jozef; Fedorko, Jakub; Pedowski, Piotr; Zapletalová, Jana (Cardiovascular and interventional radiology, 2024)
PURPOSE: Endovascular treatment (EVT) of tandem lesion (TL) in anterior circulation (AC) acute ischemic stroke (AIS) represents still a clinical challenge. We aimed to evaluate selected factors related to EVT and assess other possible predictors of good clinical outcome besides the generally known ones. METHODS: AIS patients with TL in AC treated with EVT were enrolled in the multicenter retrospective ASCENT study. A good three-month clinical outcome was scored as 0-2 points in modified Rankin Scale (mRS) and achieved recanalization using the TICI scale. Symptomatic intracerebral hemorrhage (SICH) was assessed using the SITS-MOST criteria. Logistic regression analysis was used for the assessment of possible predictors of mRS 0-2 with adjustment for potential confounders. RESULTS: In total, 300 (68.7% males, mean age 67.3 ± 10.2 years) patients with median of admission NIHSS 17 were analyzed. Recanalization (TICI 2b-3) was achieved in 290 (96.7%) patients and 176 (58.7%) had mRS 0-2. Besides the age, admission NIHSS and SICH, admission glycemia (p = 0.005, OR: 0.884) the stent patency within the first 30 days after EVT (p = 0.0003, OR: 0.219), dual antiplatelet therapy (DAPT) started within 12 h after EVT (p < 0.0001, OR: 5.006) and statin therapy started within 24 h after stenting (p < 0.0001, OR: 5.558) were found as other predictors. CONCLUSION: Admission glycemia, start of DAPT within 12 h and statin therapy within 24 h after EVT, and stent patency within the first 30 days after EVT were found as other predictors of good three-month clinical outcome in AIS patients treated with EVT for TL.
Keywords: výsledek terapie; ischemická cévní mozková příhoda; Male; Endovascular Procedures; retrospektivní studie; Middle Aged; Ischemic Stroke; Hydroxymethylglutaryl-CoA Reductase Inhibitors; endovaskulární výkony; statiny; cévní mozková příhoda; trombektomie; Stroke; Aged; mužské pohlaví; senioři; ischemie mozku; Treatment Outcome; lidé; ženské pohlaví; Humans; Retrospective Studies; Female; lidé středního věku; Thrombectomy; Brain Ischemia